As Artes De Medir: Saberes Matemáticos No Ensino Primário De São Paulo, 1890 - 1950 - Trindade, Deoclecia De Andrade [UNIFESP] (2018)
This Text Is The Result Of A Research In The History Of Mathematical Education That Has As Its Theme The Knowledge Measures In The Guidelines For Primary School In São Paulo/Brazil, 1890-1950. With The Intention Of Characterizing Historically The Mobilizations And Purposes Of Teaching Of The Knowledge Measures In The Proposals For The School, In This Study It Was Admitted As Sources The Teaching Programs Of São Paulo, Manuals And Journals Published In The Period. The Research Was Subsidized By Elements Of Cultural History (Chartier, 2000), School Culture (Julia, 2001) And More Specifically By The History Of The School Subjects (Chervel, 1990). From This Theoretical-Methodological Apparatus, Readings Of The Composition Of Different Subjects, Such As Arithmetic, Geometry And Drawing, Confirmed The Thesis That The Knowledge Measures, By Its Own Statute In The Primary School, Is Configured By Different Mobilizations And Purposes, Which Constitutes Such As "Arts Of Measuring", Which Sometimes Resulted From The Dia